2010
DOI: 10.1111/j.1469-8137.2010.03270.x
|View full text |Cite
|
Sign up to set email alerts
|

Doubled volatile organic compound emissions from subarctic tundra under simulated climate warming

Abstract: Summary• Biogenic volatile organic compound (BVOC) emissions from arctic ecosystems are important in view of their role in global atmospheric chemistry and unknown feedbacks to global warming. These cold ecosystems are hotspots of climate warming, which will be more severe here than averaged over the globe. We assess the effects of climatic warming on non-methane BVOC emissions from a subarctic heath.• We performed ecosystem-based chamber measurements and gas chromatographymass spectrometry (GC-MS) analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(147 citation statements)
references
References 53 publications
11
128
7
1
Order By: Relevance
“…This finding is in line with the results of Faubert et al (2012) who found that E. hermaphroditum was an important sesquiterpene source for the mountain birch forest floor emissions measured during the growing season. The total BVOC emission rate of the mixed heath mesocosms, 10.33 μg m −2 h −1 , was in the same range as the emission rates during the growing season from in situ measurements in Abisko: 10.9–14.61 μg m −2 h −1 for a mixed wet heath (Tiiva et al, 2008; Faubert et al, 2010) and 3.5–45 μg m −2 h −1 for an E. hermaphroditum -dominated forest floor (Faubert et al, 2012), depending on the year. The emission rates of the present experiment may be somewhat understated due to the light intensity in the growth chambers being lower than for open ecosystems under field conditions in full sunlight.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This finding is in line with the results of Faubert et al (2012) who found that E. hermaphroditum was an important sesquiterpene source for the mountain birch forest floor emissions measured during the growing season. The total BVOC emission rate of the mixed heath mesocosms, 10.33 μg m −2 h −1 , was in the same range as the emission rates during the growing season from in situ measurements in Abisko: 10.9–14.61 μg m −2 h −1 for a mixed wet heath (Tiiva et al, 2008; Faubert et al, 2010) and 3.5–45 μg m −2 h −1 for an E. hermaphroditum -dominated forest floor (Faubert et al, 2012), depending on the year. The emission rates of the present experiment may be somewhat understated due to the light intensity in the growth chambers being lower than for open ecosystems under field conditions in full sunlight.…”
Section: Discussionsupporting
confidence: 53%
“…VOCs were sampled by a push-pull system described by Faubert et al (2010, 2012) for 30 min. A transparent polycarbonate chamber (23 × 23 cm, height 25 cm), equipped with a fan to mix the headspace air, was placed on top of a water-filled groove in the aluminum frame holding each mesocosm.…”
Section: Methodsmentioning
confidence: 99%
“…It seems that the subarctic BVOC emissions increase more per unit temperature increase than the emissions from vegetation at lower latitudes (Holst et al 2010;Faubert et al 2010). Warming of the wet heath (Fig.…”
Section: Emission Of Biogenic Volatile Organic Compounds (Bvocs)mentioning
confidence: 98%
“…Warming of the wet heath (Fig. 1b) has been shown to double the emissions of monoterpenes and sesquiterpenes (Faubert et al 2010) and to increase the isoprene emissions by 50-80 % (Tiiva et al 2008;Fig. 5).…”
Section: Emission Of Biogenic Volatile Organic Compounds (Bvocs)mentioning
confidence: 99%
“…This might be caused by high isoprene emission that can increase isoprene concentration from 0 to 100 μg m −3 within 20 s based on the emission rate. Recently, growing evidence showed that isoprene emission from sedge in high-latitude wetlands was unexpectedly high (Ekberg et al, 2009;Faubert et al, 2010;Holst et al, 2010;Patrick et al, 2011;Tiiva et al, 2007aTiiva et al, , 2007b and that nitrogen deposition significantly and quickly increased sedge coverage in grassland (Bassin et al, 2007;Bowman et al, 2008) because sedge grows well in acidic soil. Moreover, our diurnal observation showed that sedge (C. korshinskyi Kom) in semi-arid grassland emitted isoprene at a high rate (N 9 mg m −2 h −1 ) compared to boreal wetlands, possibly due to drought and high temperature (N 25°C).…”
Section: Grassland Might Be a Potential Isoprene Source In Futurementioning
confidence: 99%